Kreasi Pengetahuan Organisasi : Sebuah Kajian Kritis Atas SECI Model - Arif Sugiono; Prasetya Nugeraha (Administratio, 2022)
Knowledge creation is something that is important and is a manifestation of dynamic capabilities that support organizations to achieve sustainable competitive advantage. So this study received the attention of many parties. The research method used is literature study with a phenomenological approach. The beginning of the study of the birth process of the organization which was dominated by the SECI model, which was developed by Nonaka & Takeuchi (1995). In its development, critical studies that complement the SECI model emerged, including the Boisot model, the EO-SECI model and the Salmador and Florin model. If we look closely, the four models are basically the result of the development of the model developed by Nonaka, with different points of study.